Some biochemical changes in pear fruit tissue induced by Erwinia aymlovora - Honty, Krisztina (Acta Biologica Szegediensis, 2005)
Enzyme activities (peroxidase and polyphenol oxidase) were measured in unripe resistant – Vicar of Winkfield – and susceptible – Max Red Bartlett – pear fruits during disease process caused by Erwinia amylovora infection. Samples were taken from the inoculation point and neighboring tissues during three days intervals. Host responses showed significant differences. Increases in enzymatic activities started to occur on the second day after inoculation (DAI) in the susceptible cultivar, while these changes were detectable only 3 DAI in resistant fruits. In the resistant cultivar, activities of both enzymes increased. However, in the susceptible cultivar peroxidase activity started to decrease after symptom development. Both enzyme activities were suitable markers of the susceptible and resistant host responses.